The hereditary predisposition to hip osteoarthritis and its association with abnormal joint morphology. - Pollard, T; Batra, R; Judge, A; Watkins, B; McNally, E; Gill, H; Thomas, G; Glyn-Jones, S; Arden, N; Carr, A (2013)
OBJECTIVE: Genetic factors and abnormalities of joint morphology are important in the aetiology of hip osteoarthritis (OA). The extent to which genetic influences are manifest through joint morphology has undergone limited investigation. Using a cohort with an hereditary predisposition to end-stage hip OA and a control group with no inherited risk, we aimed to identify associations with abnormal joint morphology and clinical features. DESIGN: One hundred and twenty-three individuals (mean age 52 years) with a family history of total hip arthroplasty (THA) (termed 'sibkids') were compared with 80 spouse controls. Morphology was assessed using standardised radiographs and cam, dysplasia, and pincer deformities defined. Regression modelling described the association of cohort with abnormal joint morphology, adjusting for confounders [age, gender, body mass index (BMI), OA, and osteophyte]. RESULTS: Sibkids had an odds ratio of 2.1 [95%confidence interval (CI) 1.3-3.5] for cam deformity. There were no differences in the prevalence of dysplasia or pincer deformities. In both groups, hips with cam deformities or dysplasia were more likely to have clinical features than normal hips [odds ratio (OR) 4.46 (1.8-11.3), and 4.40 (1.4-14.3) respectively]. Pincer deformity was associated with positive signs in the sibkids but not in the controls (OR 3.0; 1.1-8.2). DISCUSSION: After adjustment for confounders that cause secondary morphological change, individuals with an hereditary predisposition to end-stage hip OA had a higher prevalence of morphological abnormalities associated with hip OA. Sibkids were more likely to demonstrate clinical features in the presence of pincer deformity, suggesting that the genes are acting not only through abnormal morphology but also through other factors that influence the prevalence of pain.